Efectos agudos de la intervención musical autoseleccionada en la recuperación de las funciones autónomas y la ansiedad después de la intensidad submáxima del ciclismo a corto plazo - Ka-Lok, Iao; Chen, Yung-Sheng; Lu, Wan-An; Bezerra, Pedro (International Multidisciplinary Journal CREA, 2020)
Background: Music intervention is considered as an optimal modality to improve exercise motivation, exercise performance, and endurance capacity. The aim of this study is to investigate the acute effects of self-selected music intervention on post-exercise heart rate (HR), HR variability (HRV) and anxiety after a submaximal intensity of cycling exercise. Methods: Fifty-two healthy adults (males: n= 24, age: 20.6 ± 2 yrs; female: n= 28, 21.8 ± 2.1 yrs) were voluntarily participated this study. A counter-balanced design was used to examine submaximal intensity of cycling exercise with non-music or self-selected music trials at least 48 hours apart. Participants first visit the laboratory to determine individual self-selected music and to complete an incremental exercise test until HR response researched to 80% of heart rate reserve (HRreserve). The 80% HRreserve was used to control the exercise intensity during a subsequent 10-minute stationary cycling exercise. At the beginning of experiment, the participants performed a 5-min cycling warm-up exercise with self-pace. Afterwards, the participants rested in a sitting position for 5-min and then performed 10-min cycling exercise with intensity of 80% HRreserve. After the cycling exercise, 5-min HR recovery (HRR) and 10-min HRV was measured in a sitting position for 15-min. A situational anxiety mass scale (STAI-S) was used immediately after the cycling exercise. Music intervention was applied during 15-min post-exercise recovery. Results: The exercise HR and post-exercise HRV showed no significant differences between self-selected music trial and non-music trial in both groups. In self-selected music trial, HRR was significantly faster after the self-selected music trial than that of non-music trial in female. In addition, the STAI-S scores were significantly lower in the self-selected music trial than that of non-music trial in both groups. Conclusion: Self-selected music intervention can improve HRR in healthy female. Consideration to implement a self-selected music intervention after submaximal intensity of stationary cycling exercise to reduce post-exercise anxiety in male and female is warrant.